Climate change alters plant biogeography in Mediterranean prairies along the West Coast, USA. (11th December 2015) - Pfeifer‐Meister, Laurel; Bridgham, Scott D.; Reynolds, Lorien L.; Goklany, Maya E.; Wilson, Hannah E.; Little, Chelsea J.; Ferguson, Aryana; Johnson, Bart R.
Abstract: Projected changes in climate are expected to have widespread effects on plant community composition and diversity in coming decades. However, multisite, multifactor climate manipulation studies that have examined whether observed responses are regionally consistent and whether multiple climate perturbations are interdependent are rare. Using such an experiment, we quantified how warming and increased precipitation intensity affect the relative dominance of plant functional groups and diversity across a broad climate gradient of Mediterranean prairies. We implemented a fully factorial climate manipulation of warming (+2.5–3.0 °C) and increased wet‐season precipitation (+20%) at three sites across a 520‐km latitudinal gradient in the Pacific Northwest, USA. After seeding with a nearly identical mix of native species at all sites, we measured plant community composition (i.e., cover, richness, and diversity), temperature, and soil moisture for 3 years. Warming and the resultant drying of soils altered plant community composition, decreased native diversity, and increased total cover, with warmed northern communities becoming more similar to communities further south. In particular, after two full years of warming, annual cover increased and forb cover decreased at all sites mirroring the natural biogeographic pattern. This suggests that the extant climate gradient of increasing heat and drought severity is responsible for a large part of the observed biogeographic pattern of increasing annual invasion in US West Coast prairies as one moves further south. Additional precipitation during the rainy season did little to relieve drought stress and had minimal effects on plant community composition. Our results suggest that the projected increase in drought severity (i.e., hotter, drier summers) in Pacific Northwest prairies may lead to increased invasion by annuals and a loss of forbs, similar to what has been observed in central and southern California, resulting in novel species assemblages and shifts in functional composition, which in turn may alter ecosystem functions.